Harnessing enzyme plasticity for the synthesis of oxygenated sesquiterpenoids - Demiray, Melodi; Miller, David J.; Allemann, Rudolf K. (Beilstein Journal of Organic Chemistry, 2019)
8-Methoxy-γ-humulene, (E)-8-methoxy-β-farnesene, 12-methoxy-β-sesquiphellandrene and 12-methoxyzingiberene can be synthesised in amorphadiene synthase-catalysed reactions from 8- and 12-methoxyfarnesyl diphosphates due to the highly plastic yet tightly controlled carbocationic chemistry of this sesquiterpene cyclase.
Keywords: artemisinin; amorphadiene synthase; oxygenated terpenoids; sesquiterpenoids; substrate engineering; terpenes

(untitled) - Klayman, D. (Science, 1985)

(untitled) - White, N. J. (J. Clin. Invest., 2004)

(untitled) - Krishna, S.; Bustamante, L.; Haynes, R. K.; Staines, H. M. (Trends Pharmacol. Sci., 2008)

(untitled) - Kremsner, P. G.; Krishna, S. (Lancet, 2004)

(untitled) - Bouwmeester, H. J.; Wallaart, T. E.; Janssen, M. H. A.; van Loo, B.; Jansen, B. J. M.; Posthumus, M. A.; Schmidt, C. O.; De Kraker, J.-W.; König, W. A.; Franssen, M. C. R. (Phytochemistry, 1999)

(untitled) - Mercke, P.; Bengtsson, M.; Bouwmeester, H. J.; Posthumus, M. A.; Brodelius, P. E. (Arch. Biochem. Biophys., 2000)

(untitled) - Chang, Y.-J.; Song, S.-H.; Park, S.-H.; Kim, S.-U. (Arch. Biochem. Biophys., 2000)

(untitled) - Picaud, S.; Mercke, P.; He, X.; Sterner, O.; Brodelius, M.; Cane, D. E.; Brodelius, P. E. (Arch. Biochem. Biophys., 2006)

(untitled) - Kim, S.-H.; Heo, K.; Chang, Y.-J.; Park, S.-H.; Rhee, S.-K.; Kim, S.-U. (J. Nat. Prod., 2006)

(untitled) - Touchet, S.; Chamberlain, K.; Woodcock, C. M.; Miller, D. J.; Birkett, M. A.; Pickett, J. A.; Allemann, R. K. (Chem. Commun., 2015)

(untitled) - Cascón, O.; Touchet, S.; Miller, D. J.; Gonzalez, V.; Faraldos, J. A.; Allemann, R. K. (Chem. Commun., 2012)

(untitled) - Faraldos, J. A.; Miller, D. J.; González, V.; Yoosuf-Aly, Z.; Cascón, O.; Li, A.; Allemann, R. K. (J. Am. Chem. Soc., 2012)

(untitled) - Miller, D. J.; Yu, F.; Allemann, R. K. (ChemBioChem, 2007)

(untitled) - Faraldos, J. A.; Zhao, Y.; O'Maille, P. E.; Noel, J. P.; Coates, R. M. (ChemBioChem, 2007)

(untitled) - Huynh, F.; Grundy, D. J.; Jenkins, R. L.; Miller, D. J.; Allemann, R. K. (ChemBioChem, 2018)

(untitled) - Huynh, F.; Miller, D. J.; Allemann, R. K. (Methods Enzymol., 2018)

(untitled) - Oberhauser, C.; Harms, V.; Seidel, K.; Schröder, B.; Ekramzadeh, K.; Beutel, S.; Winkler, S.; Lauterbach, L.; Dickschat, J. S.; Kirschning, A. (Angew. Chem., Int. Ed., 2018)

(untitled) - Rising, K. A.; Crenshaw, C. M.; Koo, H. J.; Subramanian, T.; Chehade, K. A. H.; Starks, C.; Allen, K. D.; Andres, D. A.; Spielmann, H. P.; Noel, J. P.; Chappell, J. (ACS Chem. Biol., 2015)

(untitled) - Lauchli, R.; Rabe, K. S.; Kalbarczyk, K. Z.; Tata, A.; Heel, T.; Kitto, R. Z.; Arnold, F. H. (Angew. Chem., Int. Ed., 2013)

(untitled) - Beale, M. H.; Birkett, M. A.; Bruce, T. J. A.; Chamberlain, K.; Field, L. M.; Huttly, A. K.; Martin, J. L.; Parker, R.; Phillips, A. L.; Pickett, J. A.; Prosser, I. M.; Shewry, P. R.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Yu, X.-D.; Pickett, J.; Ma, Y.-Z.; Bruce, T.; Napier, J.; Jones, H. D.; Xia, L.-Q. (J. Integr. Plant Biol., 2012)

(untitled) - Yu, X.; Zhang, Y.; Ma, Y.; Xu, Z.; Wang, G.; Xia, L. (The Crop J., 2013)

(untitled) - Bhatia, V.; Maisnam, J.; Jain, A.; Sharma, K. K.; Bhattacharya, R. (Ann. Bot. (Oxford, U. K.), 2015)

(untitled) - Briggs, G. G.; Cayley, G. R.; Dawson, G. W.; Griffiths, D. C.; Macaulay, E. D. M.; Pickett, J. A.; Pile, M. M.; Wadhams, L. J.; Woodcock, C. M. (Pestic. Sci., 1986)

(untitled) - Tyagi, A. K.; Prasad, S.; Yuan, W.; Li, S.; Aggarwal, B. B. (Invest. New Drugs, 2015)

(untitled) - Shin, Y.; Lee, Y. (Toxicol. Res. (Seoul, Repub. Korea), 2013)

(untitled) - Orellana-Paucar, A. M.; Serruys, A.-S. K.; Afrikanova, T.; Maes, J.; De Borggraeve, W.; Alen, J.; León-Tamariz, F.; Wilches-Arizábala, I. M.; Crawford, A. D.; de Witte, P. A. M.; Esguerra, C. V. (Epilepsy Behav., 2012)

(untitled) - Orellana-Paucar, A. M.; Afrikanova, T.; Thomas, J.; Aibuldinov, Y. K.; Dehaen, W.; de Witte, P. A. M.; Esguerra, C. V. (PLoS One, 2013)

(untitled) - Demiray, M.; Tang, X.; Wirth, T.; Faraldos, J. A.; Allemann, R. K. (Angew. Chem., Int. Ed., 2017)

Greene's Protective Groups in Organic Synthesis - Wuts, P. G. M.; Greene, T. W. (John Wiley & Sons, Inc., 2006)

(untitled) - Rose, M. W.; Rose, N. D.; Boggs, J.; Lenevich, S.; Xu, J.; Barany, G.; Distefano, M. D. (J. Pept. Res., 2005)

(untitled) - Marco, J. A.; García-Pla, J.; Carda, M.; Murga, J.; Falomir, E.; Trigili, C.; Notararigo, S.; Díaz, J. F.; Barasoain, I. (Eur. J. Med. Chem., 2011)

(untitled) - Davisson, V. J.; Woodside, A. B.; Neal, T. R.; Stremler, K. E.; Muehlbacher, M.; Poulter, C. D. (J. Org. Chem., 1986)

(untitled) - Huang, Z.; Poulter, C. D. (Org. Synth., 1988)

(untitled) - Keller, R. K.; Thompson, R. (J. Chromatogr., 1993)

(untitled) - Bohlmann, F.; Singh, P.; Jakupovic, J. (Phytochemistry, 1982)

(untitled) - Arkoudis, E.; Stratakis, M. (J. Org. Chem., 2008)

(untitled) - Tori, M.; Aoki, M.; Asakawa, Y. (Phytochemistry, 1994)

(untitled) - Kreiser, W.; Körner, F. (Helv. Chim. Acta, 1999)

(untitled) - Sy, L.-K.; Brown, G. D. (Magn. Reson. Chem., 1997)

(untitled) - Togar, B.; Turkez, H.; Tatar, A.; Hacimuftuoglu, A.; Geyikoglu, F. (Cytotechnology, 2015)